Dyslipidaemia in children with Type 1 diabetes: Experience from a tertiary care hospital - Mohammad Raza,; Saba Shahid,; Sidra Maqsood,; Rijaa Zaheer,; Sujata Luhana, (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the lipid profile of children with type 1 diabetes, and to identify the risk factors associated with dyslipidaemia. Method: The cross-sectional study was conducted at Indus Hospital’s Korangi campus from January 2021 to March 2022, and comprised children of either gender aged up to 15 years having type 1 diabetes. Data included fasting lipid profile, thyroid-stimulating hormone level, tissue transglutaminase immunoglobulin A, serum immunoglobulin A level, urine analysis, urine-albumin creatinine ratio, and glycated haemoglobin level. Data was analysed using SPSS 21. Results: Of the 40 children, 24(60%) were boys and 16(40%) were girls. The overall median age was 8 years (interquartile range: 3.75-10 years), median body mass index was 15.9kg/m2 (interquartile range: 14.2-16.6kg/m2), and median duration of diabetes was 2 years (interquartile range: 1.7-4.5 years). Dyslipidaemia was seen in 22(55%) children, and gender had no significant association with it (p>0.05). Median total cholesterol, triglyceride, high-density lipoprotein-cholesterol and low-density lipoprotein cholesterol values were significantly higher in children with dyslipidaemia (p<0.05). Also, children with dyslipidaemia had significantly higher blood pressure values compared to those not having dyslipidaemia (p<0.03). Conclusion: Lipid profile abnormalities were common in non-obese children with type 1 diabetes, and elevated blood pressure was significantly associated with dyslipidaemia in such children. Key Words: Dyslipidaemia, Type 1 diabetes, T1D, Paediatric endocrinology, Lipid profile, Glycaemic control, Socioeconomic factors, Hypertension, Nephropathy, Celiac disease, Micro-albuminuria.